علامہ اقبال کی تصنیف جاوید نامہ کا مطالعہ : میتھوپیا کے تناظر میں: A Study of Allama Iqbal’s Javid Nama in the Context of Mythopoeia - Hussain, Fazilat (Tashkeel e Jadeed, 2026)
This paper explores Javid Nama in the light of the theory of Mythopoeia, particularly as developed by J. R. R. Tolkien. The study examines Mythopoeia as a creative act through which writers construct alternative mythic worlds with symbolic, spiritual, and intellectual dimensions. It highlights the theoretical background of Mythopoeia and its role in literary creation. The paper argues that Allama Muhammad Iqbal, through Javid Nama, creates a parallel mythological cosmos by combining Islamic, philosophical, and mystical traditions into a unified imaginative structure. The geography, spiritual journey, and classical characters of the text reflect the essential features of a mythopoeic world. The study further demonstrates that Javid Nama can be understood as a creative and symbolic cosmos that expands the scope of mythopoeic criticism in Urdu literature